Influence of industrial air pollutants on growth and physiological state of Douglas fir (Pseudotsuga menziesii) in Estonia - MANDRE, M; OTS, K (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1990-97 (0 study growth, biomass and vitality of Douglas fir [Pseudotsliga mellziesii (Mirb.) Franco], to assess its tolerance to ellvironmental changes and prospects of cultivation to increase the forest biodiversity in Estonia. Two-year-old seedlings of Douglas fir were planted in sample plots affected hy a cement plant and by oll-shah: processing enterprises and in an unpolluted control sample plot in 1990. At the end of the experiment (1917) serious inhibition in tree growth and development was indicated by an increase of the sturdiness quotient (27-31 %) and a decrease in the Dickson quality index (54-76%) in industrial areas compared with the control trees. However, an increasing proportion of needles and roots as a percentage of the total biomass in polluted areas indicated arise of compensatition mechanisms in trees to increase the assimilative mass and to improve water and nutnent availability to survive under stress.